Participants' experiences of facilitated physical activity for the management of depression in primary care. (November 2014) - Searle, Aidan; Haase, Anne M; Chalder, Melanie; Fox, Kenneth R; Taylor, Adrian H; Lewis, Glyn; Turner, Katrina M
A qualitative study was conducted within a randomised trial of facilitated physical activity for depression based on Self-Determination Theory and motivational interviewing. Interviews were held with 19 participants at 4 months, and 12 participants were re-interviewed 8 months later. The interviews were analysed in accordance with Grounded Theory using framework. Themes consisted of the following: relationship with the physical activity facilitators, mode of facilitation, impact of contact with physical activity facilitator/assimilation and future plans, change in activity, and effectiveness of physical activity facilitator techniques. Engagement in physical activity was enhanced within an autonomy-supportive environment.